Pengaruh Investment Opportunity Set dan Profitability terhadap Earnings Quality - Yuniar, Gading Tio; Andayani, Sari (Owner : Riset dan Jurnal Akuntansi, 2024)
This research on manufacturing firms listed on the Indonesia Stock Exchange in 2020-2022 aims to test the investment opportunity set, and profitability then see its effect on earnings quality. The quantitative method was chosen and applied in this paper. The research data comes from secondary data collected from the annual financial statements of the companies studied. The purposive sampling technique is used in sampling in this study. After the criteria were determined, a sample of 82 companies over three years was collected, resulting in a total of 246 data. SPSS 26 software was used to apply the multiple linear regression analysis technique. This research shows that investment opportunity set affects earnings quality positively and significantly and profitability affects earnings quality negatively.